A new way of understanding Innovation: from Insight to the historical - cultural perspective of Psychology - Casado Rojas, Eric Sebastian (InnovaG, 2018)
This article has the purpose of making an overlook on how psychological investigation has addressed innovation throughout the insights. Limitations on how the concept of insight tries to explain innovation are presented, and cultural-historical psychological theory is introduced as a more complete and enriching way of understanding the process of innovation. This analysis has Silicon Valley innovation history and culture for the last 50 years as a context. Examples are taken from two iconic companies in this field: Apple and Microsoft. The objective of this paper is to make a reflection about how the idea of insight has mythicized innovation and to offer a new psychological paradigm that can comprehend innovation as something closer and familiar to people and organizations.